Isolation of Endophytic Fungus from Bay Leaves (Syzygium polyanthum Wight.) as Antibacterials Against Bacteria Causing Digestive Tract Infections by Bioautography-TLC - Fahirah, Jihan; Herwin, Herwin; Handayani, Selpida (Journal Microbiology Science, 2025)
Salam (Syzygium polyanthum (Wight) Walp), belonging to the Myrtaceae family, are noted for their potential antibacterial properties targeting bacteria linked to gastrointestinal infections. This study aims to identify endophytic fungus isolates from bay leaves that produce antibacterial compounds effective against bacteria responsible for gastrointestinal infections, utilizing TLC-Bioautography as a method of analysis. The endophytic fungus from bay leaves was isolated, yielding 17 pure isolates. The findings from the antagonist test of pure isolates of endophytic fungus revealed two isolates with the most significant inhibitory zone diameters: IFSP-8 and IFSP-15. These isolates demonstrated effectiveness against Escherichia coli, Salmonella typhi, Shigella dysenteriae, and Vibrio cholerae bacteria. The active isolate was then extracted by liquid-liquid extraction to obtain ethyl acetate extract for the IFSP-8 and IFSP-15 isolates. The antibacterial activity results of the ethyl acetate extract, analyzed through TLC-Bioautography with a chloroform: methanol (9:1) eluent, indicated the values of Rf1 0,76; Rf2 0,56; Rf3 0,47 for the IFSP-8 isolate. In contrast, the IFSP-15 isolate exhibited the values of Rf1 0,81; Rf2 0,69; Rf3 0,56, demonstrating inhibition of bacteria responsible for gastrointestinal infections.